Misdiagnosed opacification of a hydrophobic acrylic intraocular lens. Issue 10 (October 2019) - Ahmed, Syed Naqib; Shahid, Syed Mohammed; Nanavaty, Mayank A.
Abstract : N/A: A 75‐year‐old woman was referred for decreased visual acuity resulting from "opacification of the IOL" in the immediate period after uneventful bilateral cataract surgery with single‐piece AcrySof IQ intraocular lens (IOL) implantation. A neodymium:YAG laser capsulotomy had been performed in both eyes to treat the complication. Anterior segment optical coherence tomography performed at presentation showed an opaque membrane enveloping the IOL. The membrane was peeled from the anterior IOL surface, and all adherences between the IOL and capsular bag were freed. One year later, the eyes remained stable; the uncorrected distance visual acuity was 20/20, the IOL was clear, and there was no evidence of recurrence of the membrane. Appropriate imaging for the diagnosis and surgical peeling with freeing of the adhesions between the IOL and the capsular bag were essential to the success in this case.